Aesthetic assessment of landscapes of tourist interest: case study Piraputanga Park - Aquidauana Mato Groso del Sur- Brazil - Chavez, Eros Salinas (2022)
The aesthetic characteristics of landscapes and their perception are a current topic of scientific interest, in particular applied to tourism and recreation. The following was posed as a research question: how to estimate the aesthetic values of landscapes with the use of a map of units or types of landscapes? In turn, the following objective was established: topropose a qualitative-quantitative evaluation procedure, the result of experimentation with various cartographic indicators, selected empirically, representative of observable geographic characteristics of landscapes. Different maps are presented as results, which reflect the calculation of these indicators and a summary map. The identification of the landscape sectors with the highest aesthetic values is important in the spatial planning of tourism and contributes to the conservation and management of the studied territory. In this case it is applied to the Piraputanga Park-Highway Environmental Protection Area, Aquidauana, Mato Grosso do Sul.